THE BUSINESIS ANALYSIS OF GILL NET, IN TENGGAYUN VILLAGE, BUKIT BATU SUB-DISTRICT, BENGKALIS DISTRICT OF RIAU PROVINCE - Angga Kurniawan; Lamun Bathara; Ridar Hendri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This study was aimed to analyze the costs, production of the catch andbarriers faced a gill net fisherman in developing the fishing industry in the VillageTenggayun Sub-Disrict Bukit Batu, Districk Bengkalis Riau Province. The researchresults show that fixed capital who used by fishermen gill nets in the VillageTenggayun ranges between Rp 9.234.000 - Rp 20.634.000 per year, with an averageRp.16.873,714,29. While working capital is range from Rp 12.060.000 - Rp20.836.800 per year with an average is Rp 15.429.771,43. A fixed charge issued agill net fishermen in the Village Tenggayun between Rp 3.914.666,67 - Rp5.580.666,67 per year with an average rp 4.806.864,47.While the variable cost issuedbetween Rp 12.060.000 - Rp 20.836.800 with an average Rp 15.429.771,43. Thebusiness analysis gill nets in the Village Tenggayun shows the average net income ofRp 11.915.561,90 per year , whose average score BCR 1.60, value FRR 37,26 % andvalue of PPC 2,22 years . Analysis of research shows that the gill nets business theanalysis of this research, that the gill net business has feasibility to continue improve.Key Words: gill net, business analyze, cost, income.